The Role of the Padang Lawas Police Traffic Unit in Minimizing the Number of Traffic Accidents - Mahendra, Yusril Aldi; Kusno, Kusno; Siregar, Ahmad Ansyari (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
The purpose of this research is to describe the Role of the Padang Lawas Police Traffic Unit in Overcoming Traffic Accidents in Padang Lawas City and Obstacles to the Role of the Padang Lawas Police Traffic Unit in Minimizing the number of Traffic Accidents in Padang Lawas City. This type of research is qualitative-descriptive, where the data collection technique is done through literature sources, observation, and documentation. The results showed that: first, the role of the Padang Lawas Police Traffic Unit in minimizing the number of traffic accidents, among others: 1. conducting community development in the field of traffic; 2. conducting routine patrol activities on the highway; 3. organizing the administration of completeness for drivers and motorized vehicles; 4. conducting law enforcement activities; 5. we are organizing traffic operations. Second, the inhibiting factors of the role of the Padang Lawas Police Traffic Unit in minimizing the number of traffic accidents in Padang Lawas City are: 1. Lack of public awareness of traffic order; 2. Lack of Traffic Police Professionals to carry out Tasks.